The medical radiation technologist model: a streamlined process for procedural sedations - Jennifer Meher; Julien Meyer; Annette Tracey; Housne Begum; Pria Nippak (BMC Research Notes)
Abstract Objective Procedural sedations are a growing and routine form of sedation. Some of them may not require the presence of a nurse. The purpose of this study is to assess the impact of the Medical Radiation Technologists (MRT) model, which forgo the presence of a Registered Nurse (RN), for procedural sedations in Computed Tomography biopsies. The setting was a teaching hospital that moved from an RN to an MRT model. We compared staff utilization, turnaround times and incident reports between pre and post implementation, over 19 months overall. Results No adverse events were observed under either model. Wait times were reduced by 25% from 131 to 98 min. Turnaround times were reduced by 2 min from 52 to 50 min. The joint cost of RN/MRIT was reduced by 37% per procedure, from $141 to $88. Conclusion These results suggest that the MRT model is more cost-effective without compromising quality of care. The MRT model is promising and should be extended to more facilities and other routine procedural sedations to save time and resources.